The effect of profitability, investment decisions, and sales growth on stock prices: a study on food and beverage companies - Avriliana, Winda; Prasetyanta, Agus; Herwinanto, Erfan; Kaloeti, Ade Kristianus (PHINISI, 2025)
This study investigates the influence of profitability, investment decisions, and sales growth on stock prices, with capital structure as an intervening variable in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The analysis is based on secondary data obtained from annual financial reports published on the official IDX website. From a population of 55 companies, purposive sampling resulted in 32 firms that met the research criteria. Data were analyzed using descriptive statistics, classical assumption tests, simple and multiple linear regression, t-tests, F-tests, and path analysis. The results show that profitability and capital structure significantly affect stock prices, whereas investment decisions and sales growth do not have significant direct effects. When tested simultaneously, the three independent variables collectively influence stock prices. Path analysis further indicates that the direct effects are stronger than the indirect effects, suggesting that capital structure—measured by the debt-to-equity ratio (DER)—does not mediate the relationship between the independent variables and stock prices. Theoretically, these findings reinforce signaling theory by demonstrating that profitability provides strong market signals capable of influencing stock price movements. Practically, the study offers insights for investors to prioritize profitability indicators and for managers to maintain an optimal capital structure that supports firm value.